Activation of Estrogen Receptor β in the Lateral Habenula Improves Ovariectomy-Induced Anxiety-Like Behavior in Rats - Liu, Xiaofeng; Song, Meiying; Chen, Xiaowei; Sun, Yanfei; Fan, Renfei; Wang, Liping; Lin, Weihong; Hu, Zheng; Zhao, Hua (Frontiers in Behavioral Neuroscience, 2022)
Background: Loss of estrogen due to menopause or ovarian resection is involved in the development of anxiety, which negatively impacts work productivity and quality of life. Estrogen modulates mood by binding to estrogen receptors in the brain. Estrogen receptor beta (ERβ) is highly expressed in the lateral habenula (LHb), a key site for controlling the activities of dopaminergic neurons in the ventral tegmental area (VTA) and serotoninergic neurons in the dorsal raphe nucleus (DRN) that are known to be involved in anxiety. Methods: In this study, we examined the role of LHb in the anxiolytic-like effect of estrogen in ovariectomized (OVX) rats. The establishment of OVX anxiety model was validated in behavioral tests, including elevated plus maze (EPM) and mirror chamber maze (MCM) tasks. The expression of c-Fos in the LHb neurons was analyzed by immunohistochemistry, and monoamine neurotransmitter levels in related nuclei were analyzed using high-performance liquid chromatography. Results: Estrogen-treated OVX rats showed a lower degree of anxiety-like behavior than OVX rats. OVX rats showed anxiety-like behavior and low monoamine levels in the DRN and VTA compared with sham operated and estrogen-treated OVX rats. c-Fos expression in the LHb was higher than that in the sham operated and estrogen-treated OVX rats. Intra-LHb injection of the ERβ-selective agonist diarylprepionitrile (DPN) reduced expression of c-Fos (a neuronal activity marker) and anxiety-like behavior in OVX rats, but not in normal rats, as evidenced by increased time spent in EPM open areas and the MCM mirror chamber. These changes coincided with higher levels of serotonin and dopamine in the DRN and higher dopamine levels in the VTA in OVX rats receiving intra-LHb DPN compared with those receiving vehicle injection. Conclusions: These results suggest that OVX-induced anxiety-like behavior may be associated with increased LHb activity. DPN may inhibit LHb activity to improve anxiety-like behavior in OVX rats by increasing monoamine neurotransmitter levels in the DRN and VTA.